1992
DOI: 10.1016/s0022-5347(17)37438-4
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis in Patients with End Stage Renal Failure

Abstract: Renal stones from 30 chronic hemodialysis patients were subjected to morphological study by means of microscopic examination and to constitutional analysis with infrared spectrophotometry. In 29 patients calculi could be classified into 3 main types: 1) protein stones made of pure proteins or with a protein core and less than 30% calcium oxalate (9 cases, or 30%)--they were observed predominantly in patients with primary glomerular disease, 2) oxalo-protein stones with a core of calcium oxalate and a total sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Ozasa et al [6] analyzed the molecular components of these protein stones and found that they are composed of (in decreasing order): ß 2 -microglobulin, lysozyme, serum amyloid P protein, albumin, and Tamm-Horsfall protein. Daudon et al [7] reported 4 different types of stones that they isolated from 30 of their stone-producing hemodialysis patients. Daudon et al [7] classified the stones as follows: (1) protein stones; (2) calcium oxalate stones; (3) mixed stones (protein and calcium oxalate), and (4) aluminium magnesium urate stones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ozasa et al [6] analyzed the molecular components of these protein stones and found that they are composed of (in decreasing order): ß 2 -microglobulin, lysozyme, serum amyloid P protein, albumin, and Tamm-Horsfall protein. Daudon et al [7] reported 4 different types of stones that they isolated from 30 of their stone-producing hemodialysis patients. Daudon et al [7] classified the stones as follows: (1) protein stones; (2) calcium oxalate stones; (3) mixed stones (protein and calcium oxalate), and (4) aluminium magnesium urate stones.…”
Section: Discussionmentioning
confidence: 99%
“…Daudon et al [7] reported 4 different types of stones that they isolated from 30 of their stone-producing hemodialysis patients. Daudon et al [7] classified the stones as follows: (1) protein stones; (2) calcium oxalate stones; (3) mixed stones (protein and calcium oxalate), and (4) aluminium magnesium urate stones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…55 leads to 2,8-dihydroxyadenine stone formation Daudon 56 also reported the presence of alumiand/or crystalluria. 60 The stones usually present num magnesium complex urate found in six cases in childhood and may be easily confused with uric after treatment with aluminum hydroxide in the acid stones when analyzed chemically.…”
Section: Complex Uratesmentioning
confidence: 97%